Penerapan Penerangan Jalan Umum Tenaga Surya Dengan Kendali Otomatis Pada Kampung Setaman Untuk Mewujudkan Ketahanan Energi - Wardhany, Arum Kusuma; Dwiyaniti, Murie; Nadhiroh, Nuha; Setiana, Hatib; Widjayanto, Danang (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
Kampung Setaman is one of the Climate Village (Proklim) prototypes, with work programs on greening and environmental planning, waste management, food and energy sustainability, and other community activities contributing to public resilience to climate change. Almost all of these work programs have been implemented privately, except for the energy sustainability work program, which promotes the use of renewable energy sources due to financial constraints. The lighting conditions on public street lights in Kampung Setaman continue to rely primarily on PLN sources sourced from nearby public houses, burdening the public's electricity bills. PS-TOLI conducted public service activities in the form of PJU-PLTS installation to solve the problem. Three (3) public street lighting point were installed using a PLTS source. The light is controlled automatically by a microcontroller based on the amount of sunlight and traffic density. Lamp lights can be dimmed as needed to conserve battery power. The PJU-PLTS performance test involves testing the output of the PLTS system as well as the automatic performance of the lighting lamp. In addition to the installation of street lights, the village community receives training in New and Renewable Energy as well as street lamp maintenance. It is hoped that the public will be encouraged to use PLTS as an alternative to electricity.